AB1078-HPR Telephone Follow-Up, Standardized To The Initiation of Biologic Therapy of Patients with Rheumatoid Arthritis (RA) in A Specific Unit of Biologic Therapy. Pilot Study. (15th July 2016) - Cano-Garcia, L.; Manrique-Arija, S.; Ureña, I.; Mena-Vazquez, N.; Ordoñez-Cañizares, M.C.; Romero-Barco, C.M.; Domic-Bueno, C.; Rojas-Gimenez, M.; Fuego-Varela, C.; Jimenez-Nuñez, F.G.; Irigoyen, M.V.; Coret, V.; et al.
Abstract : Objectives: To know the usefulness of follow-up call legalized at the beginning of biologic therapy and patient contact with consultation of nursing after the start of treatment. Methods: Observational study cross.Patients: We collected 120 patients who began treatment with biologic therapy, intravenous or subcutaneous from December 2013 to November 2015. Protocol: Protocol is education for self-management of subcutaneous biological therapy at the beginning of the treatment. This Protocol includes a follow-up call from the consultation of nursing that matches the first administration of the treatment at home or within 3–5 days after the first infusion. This call is made in the case of the biological subcutaneous as per guideline: etanercept (7 days), adalimumab (14 days), golimumab (28 days), tocilizumab (7days), certolizumab (14 days), abatacept (7days) either guideline prescribed in case of dose reduction. Offers the possibility of contact (telephone and e-mail) with the consultation of nurses in case of doubt or incidence during treatment and is analytical control to the month of the beginning of nurse telephone consultation. Statistical analysis: a descriptive analysis of the main variables. Results: 120 patients with RA initiated treatments were: etanercept 33, 3% (n40), adalimumab 8, 3% (10), tocilizumab sc 20% (24), abatacept sc 12, 5% (15), golimumab 13, 3% (16), rituximab 6, 7% (8), certolizumab pegol 3, 3% (4), biosimilar 2, 5% (3). In terms of the associated FAME: none 38, 3% (46), methotrexate 49, 2% (59), Leflunomide 8.3% (10), sulfasalazine 1, 7% (2), hydroxychloroquine 2, 5% (3).They were detected in the Protocol call patients with incidences 14, 16% (17): local reaction3.3% (4), pruritus 5.8% (7), upset general 0.8% (1), diarrhea 0.8% (1), constipation 0.8% (1), headache 1.7% (2). The patients called the nursing consultation to communicate incidences 10.83% (13): anemia 0.8% (1), hypertransaminasemia 1, 7% (2), implant dental 0.8% (1), bruising 0, 8% (1), inefficiency 6.7% (8). Also communicated to the consultation of nursing infections during 16.6% (20): urinary tract infection 5, 8% (7), upper respiratory tract infection 1, 7% (2), upper respiratory tract infection+herpes simplex 0, 8% (1), lower respiratory tract infection 3, 3% (4), surgical wound infection 0.8% (1), dental infection 0, 8% (1), herpes simplex 0, 8% (1), gastroenteritis 0, 8% (1), not frightening infection 1, 7% (2).Patients who started biologic therapy in the period studied only 8.3% (10) changed treatment.The emergence of new comorbidities were detected during treatment with biologic therapy 4, 16% (5): hypertension 0, 8% (1), hypertension + diabetes mellitus II 1, 7% (2), nonspecific Interstitial pneumonia 0, 8% (1), psoriasis 0, 8% (1). Conclusions: The follow-up call is a useful tool for the control of security of the new beginnings of biological agents. It could foster adherence to treatment monitoring at home and offering the possibility to communicate with the nursing. Disclosure of Interest: None declared